2021
DOI: 10.1088/1742-6596/1853/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspase-3, IL-1β and oxidative stress in Iraqi women with breast cancer

Abstract: Breast Cancer is caused by malignant tissue cells and has become one of the world’s biggest medical problems. The goal of this research was to determine the serum concentration of markers of oxidative stress that play an important role in the multiple factors involved in breast cancer development, growth, and invasion. Serum of 90 women patients (45 breast cancer and 45 benign breast tumors) and 42 healthy individuals as control group were used in this study. Serum level of MDA, PC, 8-OHdG, IL-1β and Caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…All of the above research showed results which agree with this revision. AL-Musawi et al noticed that significantly raising of serum MDA, PC, 8-OHdG, IL-1β and Caspase-3 concentrations in breast sarcoma and nonthreatening breast tumor when compared to healthy subjects 30 . Verigos et al stated that elevated levels of serum 8-OHdG and 8-NG were observed during the course of irradiation in breast malignancy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…All of the above research showed results which agree with this revision. AL-Musawi et al noticed that significantly raising of serum MDA, PC, 8-OHdG, IL-1β and Caspase-3 concentrations in breast sarcoma and nonthreatening breast tumor when compared to healthy subjects 30 . Verigos et al stated that elevated levels of serum 8-OHdG and 8-NG were observed during the course of irradiation in breast malignancy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…AL-Musawi et al . [ 57 ] demonstrated that high lipid peroxidation is an important risk factor for BC. Another study conducted in Finland by Karihtala et al .…”
Section: Discussionmentioning
confidence: 99%
“…These results mirror those of Sharma et al [56], who found that high levels of 4-HNE were observed in BC. AL-Musawi et al [57] demonstrated that high lipid peroxidation is an important risk factor for BC. Another study conducted in Finland by Karihtala et al [58] showed that 4-HNE is a marker of lipid peroxidation, which increases during breast carcinogenesis, suggesting a role of oxidative stress in the pathogenesis of BC.…”
Section: Discussionmentioning
confidence: 99%